A novel PHKA2 variant in a Chinese boy with glycogen storage diseases type IXa - Zhu, Hongdan; Zhang, Tao; Yuan, Hua; Chen, Yan; Ding, Jinlong; Ding, Haigang; Shi, Xiaoliang; Gu, Dalei; Ma, Yingying (Frontiers in Endocrinology, 2023)
Background: Glycogen storage diseases (GSDs) are a group of heterogeneous inherited metabolic disorders with an incidence of 4-5%. There are 19 types of GSDs, making diagnosis one of the greatest challenges.The proband and his parents were referred to our hospital for genetic diagnosis. Ultrasound screening suggested hepatomegaly. A novel insertion variant NM_000292 c.1155_1156insT diagnosing 删除[zhang tao]:(p. 386N>*) in PHKA2 gene was identified using trio whole exome sequencing (Trio-WES), which resulted in the codon of amino acid 386 from asparagine to termination (p. 386N>*).The 3D mutant protein structure was predicted using AlphaFold, and the results showed that the truncated PHKA2 protein contained 385 of the 1235 amino acids of the mature protein.We describe a previously unreported case of a GSDs IXa type Chinese boy caused by a novel PHKA2 variant. This clinical case contributes to the understanding of the characteristics of GSDs type IXa, and expands the variants spectrum of genes related to GSDs type IXa. Our findings demonstrated the significance of genetic testing in the diagnosis of GSDs.